2020
DOI: 10.25259/jcis_137_2020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Evaluation of Cardiac Masses in Patients with Suspicion of Cardiac Masses on Echo or Computed Tomography

Abstract: Objectives: In recent years, cardiac magnetic resonance (CMR) imaging has emerged as an important tool in the identification and characterization of cardiac masses. No imaging data on cardiac masses are available from Pakistan. We aimed to review the clinical presentation, CMR findings, and outcome of patients referred for CMR due to suspicion of cardiac masses on echocardiogram or computed tomography (CT). Material and Methods: We reviewed all the patients referred for CMR at Aga Khan University Hospital, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Notable, two cases of LA thrombi that were not demonstrated on TTE was detected on TEE. Overall, left-sided cardiac thrombi are accurately visualized on CCTA [ [16] , [17] , [18] ]. Noteworthy, the subsequent echocardiography was not performed on the same day of CCTA.…”
Section: Discussionmentioning
confidence: 99%
“…Notable, two cases of LA thrombi that were not demonstrated on TTE was detected on TEE. Overall, left-sided cardiac thrombi are accurately visualized on CCTA [ [16] , [17] , [18] ]. Noteworthy, the subsequent echocardiography was not performed on the same day of CCTA.…”
Section: Discussionmentioning
confidence: 99%
“…There is an opposite point of view regarding active surgical treatment tactics. Sultan et al concluded that conservative therapy should be preferred because surgical treatment does not affect the cause and progressive nature of the disease [ 25 ]. Unsatisfactory results in the described series may be associated with the initial preoperative severity of patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%